2023
DOI: 10.1002/mds.29401
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+–Calmodulin–Calcineurin Signaling Modulates α‐Synuclein Transmission

Abstract: Background The intercellular transmission of pathogenic proteins plays a crucial role in the progression of neurodegenerative diseases. Previous research has shown that the neuronal uptake of such proteins is activity‐dependent; however, the detailed mechanisms underlying activity‐dependent α‐synuclein transmission in Parkinson's disease remain unclear. Objective To examine whether α‐synuclein transmission is affected by Ca2+–calmodulin–calcineurin signaling in cultured cells and mouse models of Parkinson's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Our group also explored the mechanisms underlying α-synuclein transmission. Following establishment of a mouse model demonstrating the extensive spread of α-synuclein pathology from the olfactory bulb by injection of α-synuclein PFF (Uemura et al 2021 ), we showed that inhibition of the Ca2+-calmodulin-calcineurin signaling blocked the neuronal uptake of α-synuclein preformed fibrils via macropinocytosis (Ueda et al 2023 ). Thus Ca2+-calmodulin-calcineurin signaling can be a potential therapeutic target for PD.…”
Section: α-Synuclein Aggregation Propagation and Toxicity In Pd Patho...mentioning
confidence: 99%
“…Our group also explored the mechanisms underlying α-synuclein transmission. Following establishment of a mouse model demonstrating the extensive spread of α-synuclein pathology from the olfactory bulb by injection of α-synuclein PFF (Uemura et al 2021 ), we showed that inhibition of the Ca2+-calmodulin-calcineurin signaling blocked the neuronal uptake of α-synuclein preformed fibrils via macropinocytosis (Ueda et al 2023 ). Thus Ca2+-calmodulin-calcineurin signaling can be a potential therapeutic target for PD.…”
Section: α-Synuclein Aggregation Propagation and Toxicity In Pd Patho...mentioning
confidence: 99%